Estilos de liderazgo en los docentes de nivel secundario de la Red Educativa N° 06 de la región Callao - Gutiérrez Palomino, Fredi Edison (2010)
In schools considered successful, studies show that instructional leadership is one of the determining factors for the achievement of the objectives of the education system. The purpose of this research is to establish the leadership style that predominates in secondary level teachers of the Educational Network N ° 6 of Callao. The research is a descriptive methodology which sample the 99 teachers who belong to two educational institutions. The instrument used is the leadership style questionnaire CELID-A, which provides information on three leadership styles: transformational, transactional, and laissez faire. The results show that teachers transformational style predominates, with a high dominance of the subdomain Inspiration, with higher scores of female teachers.